一种基于告警数据分析的网络告警根源定位方法 (2021)
本发明公布了一种基于告警数据分析的网络告警根源定位方法，包括基于告警历史数据的建模分析步骤以及在线告警根源定位步骤；首先，通过对告警历史数据样本进行分析，挖掘网络告警之间的时序关联关系，从而建立告警元间的网络拓扑；在此基础上，将实时告警映射到所建立的网络拓扑中，基于当前告警对应的告警元在网络拓扑中的相对位置推断告警根源。本方法不需要使用网络硬件连接关系、业务逻辑依赖关系以及其他专家经验知识，开发、维护成本低；同时，本方法能够充分利用真实系统中告警发生的概率与分布特征，具有较高的分析准确性。 The invention discloses a network alarm source positioning method based on alarm data analysis. The method includes a modeling analysis step based on alarm historical data and an online alarm source positioning step, and specifically includes the following operations: firstly, analyzing an alarm historical data sample, mining a time sequence correlation relationship between network alarms, and further establishing the network topology between alarm elements; and on this basis, mapping real-time alarms into the established network topology, and deducing alarm sources based on the relative positions of the alarm elements corresponding to the current alarms in the network topology. The method does not need to use network hardware connection relationships, service logic